GRANTING OF NPK FOOD AND BOKASHI CANGKANG BEKICOT INFLUENCE TO THE GROWTH AND PRODUCTION OF SWEAT CORN PLANT (Zea mays saccharata Sturt) - Rita Mawarni (AGRIUM: Jurnal Ilmu Pertanian, 2017)
This study aims to evaluate the growth response of NPK fertilizer influence and bokashi snail shells production plant on growth and sweet corn (Zea mays saccharata L). A Randomized block design (RAK), was used while the treatment is a factorial design, which consists of two factors, are: 1. NPK fertilizers with 4 levels: N0 = 0 g/plot, N1 = 54 g/plot, N2 = 108 g/plot and N3 = 162 g/plot. 2. Fertilizer organic snail shell with 3 levels: C0 = 0 kg/plot, C1 = 2,7 kg/plot, C2 = 5,4 kg/plot. Best NPK fertilizer application are in the treatment of 162 g/plot (N3) that produce High Crop 150.58 cm, Period 13.22 leaf blade, stem diameter 29.06 mm, Production cobs/plant samples 430.67 g, Production cobs/plot 4.85 kg. Best organic granting snail shell on Bokashi treatment are 5,4 kg/plot (C2) that produce High Crop 150.67 cm, Period 13.19 leaf blade, stem diameter 28.75 mm, Production cobs/plant samples 422, 96 g, Production cobs/plot 4.76 kg. Interaction between NPK fertilizer and organic Bokashi shells not all parameter shows no significant effect on all parameters observed.Keyword : Bokashi Snail Shells, NPK Fertilizer,  Sweet Corn  (Zea mays Saccharata L)